Sources and utilization of foodstuffs in Belarusian households: results of the Grodno households survey; Ursprung und Verwendung von Nahrungsmitteln in weißrussischen Privathaushalten: Ergebnisse des "Grodno Household Survey" - Susanne Schmitz; Stephan Brosig; Josif J. Degtiarevich; Irina J. Degtiarevich; Michael Grings (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2006)
The paper is a documentation of a (non-representative) survey on the food situation of households in the Grodno region, Belarus. It covers the year between September 2000 and August 2001. The focus of the survey was on the sources of food in the households (purchase, own production, and receipt in non-monetary transactions between households) and on the utilization (consumption, feed use, sale, unpaid transfers to other households, and spoilage). The paper describes the survey design and the scope and quality of the compiled data set and it presents results of descriptive analyses. The survey households consume a well balanced diet based on potatoes and vegetables as the main staple food. 75 percent of the households use small land plots for food production and a third of the households keep livestock. Household food production provides an important contribution to food available in the households and the value of the produce represents a considerable part of average household income. Most of the self-produced food is consumed or given away in non-monetary transactions. Prices of foodstuffs differ in part significantly between different points of sale and between rural and urban areas. – – Dieses Diskussionspapier dokumentiert eine (nicht-repräsentative) Befragung über die Ernährungssituation von Haushalten in der Region Grodno in Weißrussland. Die Befragung wurde zwischen September 2000 und August 2001 durchgeführt. Der Fragebogen behandelt vorwiegend das Aufkommen von Nahrungsmitteln aus verschiedenen Quellen (Kauf, Eigenproduktion und den Erhalt von Nahrungsmitteln durch nicht-monetären Transfer zwischen Haushalten) und die Verwendung (Verzehr, Verfütterung, Verkauf, nicht-monetäre Vergabe und Verderb). Das Papier beschreibt das Studiendesign sowie den Umfang und die Qualität der erhobenen Daten. Weiterhin werden die Ergebnisse deskriptiver Analysen präsentiert. Die Ernährung der befragten Haushalte basiert auf Kartoffeln und Gemüse, wobei Kartoffeln das wichtigste Grundnahrungsmittel darstellen. 75 % der Haushalte nutzen kleine Landflächen zur Nahrungsmittelproduktion und ein Drittel hält Nutztiere. Die Eigenproduktion in den Haushalten leistet einen wichtigen Beitrag zum Nahrungsmittelaufkommen und der Produktionswert repräsentiert einen bedeutsamen Teil des durchschnittlichen Haushaltseinkommens. Der größte Teil der produzierten Nahrungsmittel wird verzehrt, gefolgt von der Vergabe in nichtmonetären Transaktionen. Die Nahrungsmittelpreise unterscheiden sich teilweise signifikant zwischen verschiedenen Einkaufsquellen und zwischen städtischen und ländlichen Gebieten.
urn:nbn:de:gbv:3:2-713
Keywords: R20; I30; 330; Belarus; Grodno; foodstuffs; food; nutrition; diet; household survey; Weißrussland; Belarus; Grodno; Ernährung; Nahrungsmittel; Haushaltsbefragung